THE INFLUENCE OF PEER FEEDBACK TOWARD STUDENTS’ WRITING ABILITY AT ENGLISH EDUCATION DEPARTMENT UNIVERSITAS MUHAMMADIYAH YOGYAKARTA - Martha Sariwulan (FPB UMY, 2015)
The students of English Education Department Universitas Muhammadiyah Yogyakarta had difficulties in the writing process in which they need feedback to solve the problem in writing. It caused the students being dependent on teacher’ feedback, hence the students need to learn being independent by doing peer feedback as learning strategy in writing. This study intends to investigate the influence of peer feedback toward students’ writing ability at English Education Department Universitas Muhammadiyah Yogyakarta. There are two research questions in this research, namely how EED UMY students’ writing ability is and what the influence of peer feedback toward students’ writing ability at EED UMY is. This study employs a quantitative research design, involving three classes of Interpretative Reading and Argumentative Writing subject at EED UMY. It involves 97 students of EED UMY as the sample of this research. The data were gathered from the questionnaire and document of students’ writing score. The measurement of peer feedback questionnaire was done with Likert Scale with five options. The data was analyzed by using descriptive and inferential statistics analysis in SPSS program, which consists of Simple Linear Regression to answer the last research question. The result revealed that the EED UMY students batch 2014 have high level of writing ability. The correlation between peer feedback and writing ability stands in low correlation category. The results present that there is only 15.8% influence of peer feedback toward students’ writing ability, while the remaining percentage is influenced by other factors. In fact, the alternative hypothesis of this research is accepted, so there is a statistical influence between peer feedback and students’ writing ability at English Education Department Universitas Muhammadiyah Yogyakarta.